Manufacture of Continuous Glass Fiber / Polylactic Acid (PLA) Composite and Its Properties - Jeong U Roh; Woo Il Lee (EPI International Journal of Engineering, 2019)
The continuous glass fiber reinforced polylactic acid (PLA) prepreg was manufactured by direct melt impregnation. The mechanical and thermal properties of PLA prepreg were observed. The properties of PLA prepreg were compared with the neat PLA and the injection molded glass fiber/PLA composite. The PLA prepreg having a fiber volume fraction of 27.7 % shows well enhanced tensile strength of 331.1 MPa, flexural strength of 528.6 MPa, and flexural modulus of 24.0 GPa. The enhancement in the heat deflection temperature (HDT) and the crystallinity were also observed. The fracture interface was inspected by FE-SEM. The degree of impregnation as a function of pulling speed was measured. The degree of impregnation at the pulling speed of 5 m/min reached over 90 % in this research.